The Missing Link Between Investments and General Foreign Policy: European Discourse Towards China - The Cases of Germany and Hungary - Voulgaris, Foivos (HAPSc Policy Briefs Series, 2021)
The aim of the present effort is to connect investment with general foreign policy. That is achieved through a qualitative analysis of the perceptions of Germany and Hungary towards China with special emphasis on the case studies of the Merger and Acquisition of Kuka and the announcement of Huawei’s expansion of activities respectively. The findings show that there does indeed exist a link but continuity is too strong to greatly change general foreign policy. What does change however is the mixture of the aspects that lead to the same result. This brief closes by attempting to learn from the reactions of Germany and Hungary towards China and to make some suggestions on how Greece should act vis-à-vis China so as to become more important as an actor in the international system.